(untitled) (Comprehensive Journal of Science, 2026)
This study examines how the translator Fadhil Habib employed translation techniques in his Arabic translation of Pride and Prejudice by Jane Austen. The aim is to demonstrate how these techniques deal with cultural and linguistic challenges in translating between English and Arabic while preserving the original meaning. The study adopts a descriptive, analytical, and comparative methodology. Selected passages from the novel and their translations are analyzed in view of translation approaches by Newmark, Byrne, Dickins and Munday. The purpose is to evaluate the effectiveness of these techniques in literary translation. The analysis shows that these techniques have overcome the translation difficulties and maintained the intended meanings. This paper highlights the importance of translation techniques in conveying literary texts from English into Arabic and offers a practical model for translators addressing cultural and linguistic challenges.